Studies of Amino Acids in Redrot Disease Infected Sugarcane (Saccharum officinarum L.) by HPLC - Raja Kumar, N.; Narayanaswamy, R. (Asian Journal of Chemistry, 2010)
An attempt has been made to detect and estimate a few amino acids present in both resistant and redrot disease infected sugarcane of different varieties using HPLC. Five amino acids namely tyrosine, methionine, isoleucine, leucine and lysine play an important role in sugarcane crops. A possible correlation between the variation of free amino acids and diseased conditions have been discussed.